Factors influencing Arab and Non-Arab customers' satisfaction towards banks in Malaysia / Nada Tareq Al-Mallah - Al-Mallah, Nada Tareq (2012)
In this study different dimensions of service quality, customer expertise’s and customer demographics have been considered and viewed as a direct determinant of customer satisfaction with an indirect determinant of service value moderating the service quality dimension in the process leading to overall customer satisfaction among Arabs and non- Arabs customers towards Malaysian Banks, to emphasize on the impact of ethnicity over customer satisfaction as many researches had shown like (Snow et al., 1996; Lassar, Manolis & Winsor, 2000; Lopez, Hart & Rampersad; 2007; Hart, Lopez, Jalbert, Jalbert & Rampersad, 2007). An empirical research methodology was used; model was proposed, online and self administrated survey was conducted. This explanatory study uses factor analysis to identify the most important factors of customer satisfaction. A modified SERVQUAL scale is utilized to determine the functional dimensions of service quality and customer satisfaction, and five- point Likert scale for customer expertise is used. The findings indicate that different ethnic group reflects different level of satisfaction, also the study findings shows that the relational dimensions of service quality appears to be linked to customer satisfaction in the presence of service value, and customer expertise is positively related to satisfaction, it was identical to results of previous studies, while some but not all of the demographic variables are positively related to customer satisfaction such as age, education, income...etc.